Social rank pathways to disordered eating: exploring maladaptive regulation processes of the experience of threat and shame - Mendes, Catarina Borralho (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação